Hemoadsorption in a Case of Severe Septic Shock and Necrotizing Fasciitis Caused by Nontraumatic Renal Rupture due to Pyelonephritis with Obstructive Uropathy - Lampros Kousoulas; Uwe Wittel; Stefan Fichtner-Feigl; Stefan Utzolino (Case Reports in Critical Care)
Background. Nontraumatic renal rupture due to pyelonephritis with obstructive uropathy is an uncommon but life-threatening situation. Case Presentation. A 25-year-old female presented to the emergency department with acute worsening of abdominal pain that began four weeks earlier. She was found to have peritonitis, leukocytosis, severe lactic acidosis, and a pronounced anemia and imaging was consistent with nontraumatic renal rupture with retroperitoneal abscess, perforation of the colon, and severe necrotizing fasciitis of the right lower limb. She underwent a right nephrectomy, a right hemicolectomy, surgical debridement of the retroperitoneum, and an upper thigh amputation. Due to severe septic shock and rhabdomyolysis with acute renal failure we performed a combined treatment of hemoadsorption using a Cytosorb hemoadsorber and continuous venovenous hemodialysis (CVVHD). Subsequently the patient recovered and was discharged home with no signs of infections and with normal renal function. Conclusion. We present a case of pyelonephritis with nontraumatic renal rupture leading to necrotizing fasciitis with osteomyelitis of the lower limb. The early treatment of the patient with a Cytosorb hemoadsorber led to a rapid hemodynamic and metabolic stabilization and preservation of the renal function, suggesting that hemoadsorption might be a rescue therapy in patients with severe septic shock and traumatic rhabdomyolysis.